Effect of Nifedipine in Preventing Ovarian Hyperstimulation Syndrome through TRPC1 Ion Channel Inhibition - Kocal, Emel; Atilgan, Remzi; Pala, Sehmus; Aslan, Melike; Kuloglu, Tuncay; Ilhan, Nevin; Bircan, Gizem Kaymaz (Springer Heidelberg, 2025)
Ovarian hyperstimulation syndrome (OHSS) is a life-threatening complication that usually develops as a result of triggering ovulation with human chorionic gonadotropin (hCG) after gonadotropin treatment, and in whose pathophysiology vascular endothelial growth factor (VEGF) and inflammatory mediators play a role. Nifedipine, used especially in the treatment of hypertension, is a calcium channel blocker. Nifedipine also has anti-inflammatory effects via transient receptor potential canonical (TRPC1) ion channel inhibition. VEGF also regulates the angiogenic process through TRPC channels. In our study, we investigated the potential of nifedipine to prevent OHSS due to its TRPC1 blocking effect and anti-inflammatory effects. A total of 28 rats were randomly divided into four equal groups. Group (G) 1 control group (n = 7). Rats in G2 (n = 7) were administered 30 IU pregnant mare serum gonadotropin for 4 days and OHSS was induced by administering 30 IU hCG on the fifth day. Rats in G3 (n = 7) were induced to have OHSS and were given 100 mu g/kg oral cabergoline, while rats in G4 (n = 7) were induced to have OHSS and were given 20 mg/kg intraperitoneal nifedipine. On the fifth day, all rats were decapitated and VEGF, interleukin (IL)-1 beta, IL-6, tumor necrosis factor (TNF)-alpha, and hypoxia-inducible factor (HIF)-1 alpha levels were measured in their serum and tissues. TRPC1 gene expression and immunohistochemical analysis were performed in ovarian tissue. We showed that nifedipine inhibited VEGF and some inflammatory factor levels more than cabergoline. We showed that nifedipine may achieve these effects through TRPC1 blockade and suppression of inflammatory factors.
Keywords: OHSS; Rat; Nifedipine; TRPC1; VEGF